2015
DOI: 10.1080/15287394.2015.1010466
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression Levels of Neurodevelopmental Proteins in Fetal Brains of BTBR T+tf/J Mice with Autism-Like Behavioral Characteristics

Abstract: Autism is a brain developmental disorder with characteristics of social interaction defects, language and communication dysfunction, and repetitive behavior. Occurrence of autism is continuously increasing, but the cause of autism is not clearly defined. Genetic linkage or environmental factors were proposed as sources for pathogenesis of autism. BTBR T+tf/J (BTBR) mice were reported as an appropriate animal model for autism investigation because of their similarities in behavioral abnormalities with human aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Interestingly, we found that peripheral BDNF levels were higher in the ASD samples from childhood but not from adulthood. Evidence from animal models of ASD suggests that BDNF levels increase in the foetal brain 29 30 . In the ASD model of sodium valproate (VPA) exposure in utero, VPA administration has been shown to increase BDNF protein levels in the feotal mouse brain 5- to 6-fold in vitro and in vivo 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that peripheral BDNF levels were higher in the ASD samples from childhood but not from adulthood. Evidence from animal models of ASD suggests that BDNF levels increase in the foetal brain 29 30 . In the ASD model of sodium valproate (VPA) exposure in utero, VPA administration has been shown to increase BDNF protein levels in the feotal mouse brain 5- to 6-fold in vitro and in vivo 29 .…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was obtained for NGF (nerve growth factor) between the two strains (Hwang et al 2015). The upregulation of BDNF expression at an early developmental stage (in stark contrast to the BDNF signaling deficiency in later life of BTBR mice) is in line with clinical data showing increased plasma BDNF in children with ASD (Wang M. et al 2015).…”
Section: Altered Gene and Protein Expression In The Btbr Mousementioning
confidence: 95%
“…Abs were found to be elevated in the striatum and substantia nigra regions, while increased deposition of IgG 1 was found in the cerebellum, cortex, hippocampus and striatum (Kim et al 2016). Hwang and colleagues (Hwang et al 2015) looked at levels of IgG isotypes deposited in fetal brain of BTBR mice. All but IgG 1 were elevated in comparison to FVB fetal brains.…”
Section: Other Physiological Aberrations Reported For the Btbr Strainmentioning
confidence: 99%
“…Inflammatory mediators profile, including levels of immunoglobulins (Ig)G in the fetal brain of BTBR mice, have been characterized. BTBR mice had lower levels of glial fibrillary acidic protein (GFAP), and higher levels of brain-reactive immunoglobulin (IgG), except IgG1, than FVB mice [ 33 ]. This is in contrast with reports in humans showing increased GFAP levels in children with ASD [ 34 ].…”
Section: Pre-clinical Research: Inflammation In Animal Models Of Asd mentioning
confidence: 99%